Analisis Customer Relationship Management (CRM) Dalam Meningkatkan Jumlah Nasabah KSU BTM Surya Amanah Jombang - Susilawati, Ririn; Silmi, Ziyadatul Iffatis (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
Today’s marketing world not only focuses on the quality of products or services but also focuses on the quality of company relationships with customers. Companies that keep relationship afloat with customers have the power to compete with competitors in the same area. Marketing strategies that have the essense of maintaining relationships and increasing customer quantity are customer relationship management. The purpose of this study is to understand and describe financing murabahah and customer analyses management in increasing customer loyalty. The study uses descriptive qualitative research with tehniques of observation, interview and documentation collection. The results of this study are known that the murabahah financing prosedure was undertaken systematically and implementing CRM through prime service by combining aspects of the process, people and technologies, which have resulted in increased financing loyalty to BTM Surya Amanah Jombang.